2012
DOI: 10.1002/bdd.1807
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of a primaquine prodrug without red blood cell membrane destabilization property

Abstract: Primaquine is an important therapeutic resource for malaria treatment and it has wide activity against several pathogens. The haematotoxicity of primaquine is the major problem for its therapeutic application. This effect is aggravated by repeated use at high doses and by the wide fluctuation of plasma levels after administration. The primaquine prodrug (Phe-Ala-PQ) was planned in order to modify the pharmacokinetics and toxicity of primaquine. The in vitro conversion of Phe-Ala-PQ to primaquine, and the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Phe-Ala-PQ, for example, is a prodrug containing the dipeptide phenylalanine-alanine as carrying group which shows in vitro and in vivo anti T. cruzi effects [17], [19]; however, the antimalarial effect has not yet been described. We have found that this compound causes less erythrocyte osmotic fragility and shows less fluctuation of plasma concentration [17]. The variation in PK parameters in Phe-Ala-PQ is due in part to increased water solubility caused by the introduction of the dipeptide.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Phe-Ala-PQ, for example, is a prodrug containing the dipeptide phenylalanine-alanine as carrying group which shows in vitro and in vivo anti T. cruzi effects [17], [19]; however, the antimalarial effect has not yet been described. We have found that this compound causes less erythrocyte osmotic fragility and shows less fluctuation of plasma concentration [17]. The variation in PK parameters in Phe-Ala-PQ is due in part to increased water solubility caused by the introduction of the dipeptide.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in PK parameters in Phe-Ala-PQ is due in part to increased water solubility caused by the introduction of the dipeptide. This modification allows sustained release of PQ by bioconversion of the prodrug, and it prolongs the mean residence time of PQ increasing its half life after oral administration [17]. All these effects are due to alterations in physico-chemical parameters such as partition coefficient (log P).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations